MENINGKATKAN KREATIVITAS MELALUI METODE PEMBERIAN TUGAS MELIPAT KERTAS PADA SISWA KELOMPOK B TK ISLAM YLPI MARPOYAN PEKANBARU - Akmal, Aulia (UIR PRESS, 2018)
Kindergarten is an educational institution intended for children aged 4–6 years to carry out a learning process so children can develop their potential early on. Children must obtain their motor, intellectual, social and emotional stimuli according to their age level. From an early age, children are introduced to folding paper. In kindergarten learning, most teachers pay less attention to children's learning outcomes towards this one learning. Teachers often use paper folding as a relaxation learning for children who pay less attention to children's learning outcomes towards this one learning. Teachers often use paper folding as a relaxation study for children regardless of the results of children's work so that it is found that children's work in learning to fold paper seems without direction. The purpose of this study was to find out that folding paper can increase children's creativity in the B3 Group of Islamic Kindergarten YLPI Marpoyan, Pekanbaru. This study is a Classroom Action Research (CAR) conducted in two cycles, in each cycle of three meetings. The results showed that the paper folding development activities in the B3 group with the assignment of tasks had succeeded and increased. Increasing children's creativity through paper folding activities can be seen in cycle II. Hand speed coordination with the eye in carrying out the activities between the hand and eye are interconnected, careful, concentration on the tasks of activities carried out by students at the time of the activity activities hope that the resulting work is better, neater and faster in completing.